1D AND 2D NMR STUDIES OF BENZYL O–VANILLIN - Mohammed Hadi Al–Douh; Shafida Abd Hamid; Hasnah Osman (Indonesian Journal of Chemistry, 2008)
The reaction of o-vanillin A with benzyl bromide B2 in acetone as the solvent and K2CO3 as a base in the presence of tetra-n-butylammonium iodide (TBAI) as catalyst formed benzyl o-vanillin, C. The complete assignments of C using PROTON, APT, DEPT-135, COSY, NOESY, HMQC and HMBC NMR in both CDCl3 and acetone-d6 are discussed, and the coupling constants J are reported in Hertz (Hz).